Scaling Up Climate Services for Farmers in Africa and South Asia: Workshop Report - Tall, Arame; Jay, A.; Hansen, James (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This report summarizes the proceedings of the workshop “Scaling Up Climate Services for Farmers in Africa and South Asia,” held in Saly, Senegal on December 10-12, 2012. The workshop brought together more than 100 experts from 30 countries and roughly 50 institutions to grapple with the challenge of supporting vulnerable farming communities through the production, communication, delivery and evaluation of effective agrometeorological information and advisory services; and to identify practical actions to address those challenges at scale.